Exploring EFL Pre-Service Teachers’ Critical Incidents in Microteaching Practicum - Maharsi, Ista (Vision: Journal for Language and Foreign Language Learning, 2023)
This paper analyzes pre-service teachers’ critical incidents as reflected in their e-portfolios during their teaching simulation in the microteaching course. Three cycles of teaching practice were scheduled for each student-teacher. Thirty-six student-teacher critical incidents and e-portfolios were analyzed. Data were collected mainly from their e-portfolios containing their critical incidents. In addition, observations and focus group discussions were conducted to triangulate and confirm the students’ critical incidents. Results showed that of the total 130 critical incidents, 60 occurred in their first, 38 in their second, and 34 in their third teaching cycle. It indicates that the pre-service teachers struggle more at the beginning of their teaching practicum, go through the learning process, and develop their understanding of teaching. In addition, the student-teachers are empowered by obtaining the ability to sense the theoretical and practical gaps in teaching, indicate teaching problems and complexity, become aware of the challenging classroom management issues, and future professional development. This study highlights the importance of reflective practices such as critical incident analyses to be induced in teacher training programs. Through critical incident identification, pre-service teachers are trained to develop their reflection-on-action skills, pedagogical awareness, and choices and sharpen their sense of teaching problems, particularly when encountering theory-practice gaps.